Impact of Service-Learning on Student Counselors’ Self-Reported Measures of Program Evaluation, Counselor Advocacy, and Interprofessional Education - Jessica Lloyd-Hazlett; Cory Knight; Emily Horton; Samantha Airhart-Larraga (Teaching and Supervision in Counseling, 2022)
Abstract: Academic service-learning encompasses a reciprocal relationship among university and community partners. Service-learning can familiarize student counselors with future client populations, community resources, and other service providers. Service-learning pedagogy is flexible and may be particularly useful to promote development in counselor competencies more abstractly related to day-to-day client services, including program evaluation and professional advocacy. Interprofessional education serves as a means of enhancing interprofessional collaboration and, in turn, the well-being of individuals seeking healthcare services. Service-learning may provide a vehicle to promote interprofessional education, however, researchers have not yet explored this connection. This quantitative research project evaluates pre- and post- changes of 18 participants using the Effective Practices Survey, Advocacy Competencies Self-Assessment scale to measure experiences in program evaluation, counselor advocacy, and interprofessional education. Results indicate that student counselor scores significantly increased for each of the three variables of interest, with the largest changes observed for counselor advocacy. What is the public significance of this article? Academic service-learning leverages relationships between university and community partners. Service-learning may be a particularly effective pedagogical strategy to promote applied and potentially abstract concepts. This article explores the impact of engagement in an experiential service-learning project on 18 student counselors’ learning outcomes related to program evaluation, counselor advocacy, and perceptions of interprofessional education.
Keywords: service-learning; interprofessional education; advocacy; program evaluation